Study Of The Political Dynasty “Native Tenganans” In The Government Of Tenganan Pegringsingan Traditional Village Bali - I Ketut Oka Setiawan; Tetti Samosir (JURNAL HUKUM SEHASEN, 2024)
The Indonesian state is a unitary state in the form of a republic. Still, in practice, there are dynastic politics of the "Native Tenganans" in the government of the traditional village of Tenganan Pegringsingan Bali. This contradictory situation needs to be questioned regarding its legality, occurrence, and how to maintain this political dynasty. This short research used descriptive analysis with an empirical normative approach. Data is presented in narrative form and analyzed qualitatively. The research results revealed that the legality of the "Native Tenganans" political dynasty in village government can be found starting from the basic state law and Law No. 6 of 2014 concerning villages. This political recognition also includes the existence of the political dynasty of Native Tenganans. In line with the country's politics, the origins of the Native Tenganans dynasty were obtained from the king of Karangasem as a reward for providing services to the ancestors of the Native Tenganans for a piece of territory (village) complete with its system of government. The way to maintain the political dynasty of the Native Tenganans is determined by establishing a militant character through Matruna Nyoman Education for the next generation, requiring their descendants to enter into endogamous marriages, and determining the benefits of land in the village area as joint ownership for the welfare of its citizens.